#TITLE_ALTERNATIVE# - A. MALAU (NIM 15002155), HERLAND
This study presents seismic hazard analysis in Yogyakarta city to estimate peak baserock acceleration (PBA) for 500 year return period and soil dynamic response to estimate acceleration in surface. This study also used to look the effect of Opak fault in PBA estimating Seismic hazard analysis is acted with Probabilistic Seismic Hazard Analysis (PSHA) method using EZ FRISK computer program. Seismic source considered are the latest earthquake to a depth of 200 km within radius 500 km from Yogyakarta. These seismic sources are modeled as subduction and shallow crustal zone. To cover uncertainties, logic tree model is utilized. Seismic parameters are calculated by the method of least square, Weichert(1980) and Kijko & Sellevol (1989). 4 atenuation models are chosen such as, Youngs (1997) atenuation models for subduction zone, then Boore et. Al.(1997), Sadigh (1997) and Idriss (2004) are choosen for shallow crustal zone. The result of the analysis shows that the PBA og Yogyakarta city is 0.300 g for 500 year return period. Ground response analysis is conducted to know the response of local soil condition to the motion of the of the bedrock using one dimensional shear wave propagation using NERA computer program. Sintetik input motion used in this analysis is from spectral matching from other eathquuake motion in other countries. This result of site response analysis is compared to the UBC standard code.